Thrombotic microangiopathy resulting from neglected blood pressure control - Jeong Sang Ku; Won Kim; Sik Lee; Myoung Jae Kang; Sung Kwang Park; Kyung Pyo Kang (The Korean Society of Nephrology, 2014)
Hypertensive nephrosclerosis is usually associated with chronic hypertension, which increases the risk of progressive renal disease. Among the causes of malignant hypertension, thrombotic microangiopathy is complicated and is associated with renal dysfunction at the time of diagnosis. In this case, a young man with hypertension presented with renal failure and thrombocytopenia in the emergency department. This case emphasizes the importance of early recognition of renal failure and thrombocytopenia among patients with uncontrolled hypertension.